2017
DOI: 10.1007/s00284-017-1249-3
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of a Biosurfactant-Producing Bacillus subtilis UMX-103 Isolated from Hydrocarbon-Contaminated Soil in Terengganu, Malaysia

Abstract: The draft genome here presents the sequence of Bacillus subtilis UMX-103. The bacterial strain was isolated from hydrocarbon-contaminated soil from Terengganu, Malaysia. The whole genome of the bacterium was sequenced using Illumina HiSeq 2000 sequencing platform. The genome was assembled using de novo approach. The genome size of UMX-103 is 4,234,627 bp with 4399 genes comprising 4301 protein-coding genes and 98 RNA genes. The analysis of assembled genes revealed the presence of 25 genes involved in biosurfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…In this study, we have identified biosurfactant producing genes and corresponding orfs of Bacillus tequilensis such gene SrfAD, SrfAC, SrfAA and the sequence of the same was deposited in Genbank database with accession MUG02427.1, MUG02428.1, MUG02429.1,MUG03515.1 respectively. [18] Considering the biosurfactant producing genes described in various literatures, we classified the through the NRPS multi-enzyme complex, comprising adenylation,condensation, and thiolation domains responsible for the activation of amino acids and peptide chainelongation.…”
Section: 6metabolism Of Biosurfactant Producing Genesmentioning
confidence: 99%
“…In this study, we have identified biosurfactant producing genes and corresponding orfs of Bacillus tequilensis such gene SrfAD, SrfAC, SrfAA and the sequence of the same was deposited in Genbank database with accession MUG02427.1, MUG02428.1, MUG02429.1,MUG03515.1 respectively. [18] Considering the biosurfactant producing genes described in various literatures, we classified the through the NRPS multi-enzyme complex, comprising adenylation,condensation, and thiolation domains responsible for the activation of amino acids and peptide chainelongation.…”
Section: 6metabolism Of Biosurfactant Producing Genesmentioning
confidence: 99%
“…The genes, rmlA, rmlB, rmlC and rmlD are only present in UMX − 103 strains whereas, sigA, DnaK and LytR are present speci cally in Bacillus strain. Besides, the genes comA, comP, rpoN, abrB and ResD are presented in both UMX-103 and B. subtilis 168 [18]. Based on the above literature biological annotation, we have identi ed DnaKandLytRgenes from Bacillus tequilensis and the sequence were deposited in NCBI with accession MUF99480.1 and MUG01692.1 respectively.…”
Section: Metabolism Of Biosurfactant Producing Genesmentioning
confidence: 99%
“…In this study, we have identi ed biosurfactant producing genes and corresponding orfs of Bacillus tequilensis such gene SrfAD, SrfAC, SrfAA and the sequence of the same was deposited in Genbank database with accession MUG02427.1, MUG02428.1, MUG02429.1,MUG03515.1 respectively. 3. srfA [16] 4. rhlB [16] 5. cfp [17] 6. srfAA [18] 7. srfB [18] 8. srfAB [18] 9. srfAD [18] 10. Spf [18] 11. ppsB [18] 12. ppsC [18] 13. ppsD [18] 14.…”
Section: Metabolism Of Biosurfactant Producing Genesmentioning
confidence: 99%
See 2 more Smart Citations